2012
DOI: 10.1136/heartjnl-2012-302005
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of premature ventricular complexes in adults without clinically apparent heart disease: a meta-analysis and systematic review

Abstract: Most studies on PVC prognosis in 'normal hearts' did not use advanced tests to rule out structural heart disease. Among these patients, PVCs are associated with a worse cardiovascular outcome if patients are older and have higher cardiovascular risk, suggesting that the poor prognosis studies may have inadvertently included patients with occult structural heart disease, the population in which PVCs are known to confer adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 35 publications
1
50
0
2
Order By: Relevance
“…33 Although the clinical impact of these previously unknown arrhythmias in TAVR candidates remains to be elucidated, short episodes of AF/AT have been associated with an increased risk of stroke in patients with implantable devices and in the overall population, 11,34 and occurrences of ventricular arrhythmias and paroxysmal AVB have been described as predictors of sudden cardiac death and adverse cardiac events. 9,22,35 Interestingly, ≈1 in 10 TAVR candidates had a change in therapy related to the diagnosis of previously unknown arrhythmic events, highlighting the importance of monitoring such patients before the TAVR procedures. Whether or not early therapy in patients with paroxysmal events may be associated with a potential benefit in patients undergoing TAVR should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 Although the clinical impact of these previously unknown arrhythmias in TAVR candidates remains to be elucidated, short episodes of AF/AT have been associated with an increased risk of stroke in patients with implantable devices and in the overall population, 11,34 and occurrences of ventricular arrhythmias and paroxysmal AVB have been described as predictors of sudden cardiac death and adverse cardiac events. 9,22,35 Interestingly, ≈1 in 10 TAVR candidates had a change in therapy related to the diagnosis of previously unknown arrhythmic events, highlighting the importance of monitoring such patients before the TAVR procedures. Whether or not early therapy in patients with paroxysmal events may be associated with a potential benefit in patients undergoing TAVR should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsustained VT Premature ventricular contractions (PVCs) and non sustained VT may be associated with occult structural heart disease and with longterm reduced survival in unselected populations. 253 Even in otherwise normal hearts, PVCs and nonsustained VT may over time lead to tachycardiainduced cardiomyopathy. 254 Further eval uation and treatment may be warranted in some situa tions 254 such as determining the origin of the VT, which may help guide further therapy such as ablation.…”
Section: Ventricular Tachycardiasmentioning
confidence: 99%
“…Among these patients, ventricular ectopics are associated with worse cardiovascular outcomes if the patients are older and have higher cardiovascular risk, suggesting that the poor prognosis studies may have inadvertently included patients with occult structural heart disease, the population in which ventricular ectopics are known confer adverse outcomes. 9 While the study on a cohort of the Multiple Risk Factor Intervention Trial (MRFIT) 10 reported that the presence of ventricular ectopics identified on a rest two-minute ECG rhythm strip was associated with a high risk for sudden death in apparently healthy subjects over a 7.5 year follow-up. Similar outcomes were reported in apparently healthy subjects in the Framingham Heart Study 11 whereby ventricular ectopics were associated with a twofold increase in the risk of all cause mortality, myocardial infarction and cardiac death.…”
Section: Discussionmentioning
confidence: 99%